2001
DOI: 10.1089/089771501750357627
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Single- and Double-Strand DNA Breaks After Traumatic Brain Injury in Rats: Comparison ofIn SituLabeling Techniques Using DNA Polymerase I, the Klenow Fragment of DNA Polymerase I, and Terminal Deoxynucleotidyl Transferase

Abstract: DNA damage is a common sequela of traumatic brain injury (TBI). Available techniques for the in situ identification of DNA damage include DNA polymerase I-mediated biotin-dATP nick-translation (PANT), the Klenow fragment of DNA polymerase I-mediated biotin-dATP nick-end labeling (Klenow), and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL). While TUNEL has been widely utilized to detect primarily double-strand DNA breaks, the use of PANT to detect primarily single-strand DNA break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“…PANT labeling was primarily nuclear and, based on the size, morphology, and location of the stained cells, appeared to occur in neurons. Previous dual-label studies in rats have detected PANT in mostly neuronal phenotypes (Clark et al 2001). PANT was not detected in the contralateral hemispheres, or in deeper brain regions after CCI.…”
Section: Initiators Of Parp-1 and Parp-1 Activation In Injured Brainmentioning
confidence: 58%
See 2 more Smart Citations
“…PANT labeling was primarily nuclear and, based on the size, morphology, and location of the stained cells, appeared to occur in neurons. Previous dual-label studies in rats have detected PANT in mostly neuronal phenotypes (Clark et al 2001). PANT was not detected in the contralateral hemispheres, or in deeper brain regions after CCI.…”
Section: Initiators Of Parp-1 and Parp-1 Activation In Injured Brainmentioning
confidence: 58%
“…PANT assay PANT was performed as previously described (Clark et al 2001). Briefly, paraffin-embedded 5-lm coronal sections were deparaffinized then incubated in 3% Triton X-100 (Sigma, St Louis, MO, USA) at room temperature for 1 h, then placed in 3% H 2 O 2 and 30% methanol in PBS for 20 min.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies reported soma shrinkage with pyknotic nuclei [26] (i.e. condensation of chromatin leading to a shrunken nucleus) and damaged DNA [27,28] . However, these alterations are delayed compared to the axonal damages, suggesting that they may be associated with a secondary injury related to axonal swellings.…”
Section: Research Highlightmentioning
confidence: 99%
“…terminal deoxynucleotidyl-transferase-mediated dUDP nick end-labeling (TUNEL) or in situ nick translation (ISNT) (Clark et al, 2001;Gavrieli et al, 1992;Rink et al, 1995). However, experimental studies have shown that single-stranded DNA (ssDNA) degradation precedes DNA double-strand breaks (DNAdsb) during a delayed neuronal death process caused by reperfusion after transient brain ischemia or intracerebral hemorrhage, possibly due to oxidative stress (Chen et al, 1997;Gong et al, 2001;Love, 1999;Nakamura et al, 2005).…”
Section: Brain Neuronal Apoptosis In Human Deathmentioning
confidence: 99%